Cranial Nerve Enhancement in Multiple Sclerosis Is Associated With Younger Age at Onset and More Severe Disease - Haider, Lukas; Chan, Wei-Shin Evelyn; Olbert, Elisabeth; Mangesius, Stephanie; Dal-Bianco, Assunta; Leutmezer, Fritz; Prayer, Daniela; Thurnher, Majda (Frontiers in Neurology, 2019)
Background: The overall frequency of cranial nerve pathology, including cranial nerves other than the trigeminal nerve, as well as its relation to brainstem lesion formation on magnetic resonance imaging (MRI) and clinical correlates in multiple sclerosis (MS) is unknown. Objective: We aimed to determine the frequency of cranial nerve enhancement on MRI, and its association with brainstem lesion formation and clinical outcomes. Methods: We retrospectively analysed in 183 patients (RRMS: 156, SPMS: 15, PPMS: 6, CIS: 6) 651 MRIs (76.5% on the identical scanner Siemens Trio Tim, 3T with identical MRI protocols). Frequencies of cranial nerve enhancement on post contrast T1-weighted MRIs were compared to lesion counts and the MS-severity-score. Results: Cranial nerve enhancement was present in 8.2% of the analysed MS patients (oculomotor-nerve: 1.1%, trigeminal-nerve: 2.7%, abducens-nerve: 2.2%, facial-/vestibulocochlear nerve: 1.6%, vagal-nerve: 0.5%). Of those, 13% suffered from repeated episodes and 27% exhibited a cranial nerve enhancement duration of >12 months. Age at MS onset was lower in patients with cranial nerve enhancement, 23 vs. 28 years, p=0.049. The MS-severity-score, 5.15 vs. 0.88 (p=0.019), the T2 brainstem-, 1 vs. 0 (p=0.041), and the total intracranial contrast-enhancing lesion counts, 2 vs. 0 (p=0.000), were higher in patients with cranial nerve enhancement, compared to age-, disease duration-, and gender- matched MS patients. Conclusions: Cranial nerve enhancement, present in 8.2% of our patients, was associated with a younger age at MS onset, brainstem lesions, and a more severe disease course.